Design on Hybrid Test System for Dynamic Performance of Viscoelastic Damping Material and Damper - Guo, Ying-Qing; Li, Yang; Yang, Tian-Tian; Jing, Xingjian; Chen, Xiao; Luo, Ying (Frontiers in Materials, 2019)
The viscoelastic material is one of most popular shock absorbing materials for mitigating vibrations of building structures due to earthquake. Its dynamic performance is affected by the temperature, the excitation frequency and the excitation amplitude. Therefore, in order to study the nonlinear dynamic performance of the viscoelastic materials, a hybrid test system using the electric exciter is proposed, in which the electric exciter is the actuator, MATLAB is used for the simulation of the numerical substructure and the communication between the upper computer and the lower machine, and STM32 single-chip microcomputer is used to control the work state of the electric exciter. Based on the equivalent force control method and the incremental PID control algorithm, a controller is designed to make sure the electric exciter produces accurate control forces to the nonlinear test component in the physical substructure. It can be shown from the test results that the developed whole hybrid test system is feasible and effective.